ϕ-modes of neutron stars in a massless scalar–tensor theory - Blázquez-Salcedo, Jose Luis; González-Romero, Luis Manuel; Khoo, Fech Scen; Kunz, Jutta; Preut, Vincent (Frontiers in Astronomy and Space Sciences, 2022)
Scalar–tensor theories allow for a rich spectrum of quasinormal modes of neutron stars. The presence of the scalar field allows for polar monopole and dipole radiation, as well as for additional higher multipole modes led by the scalar field. Herein, we present one family of the modes which are dominated by the scalar fields, the scalar-led ϕ-modes computed numerically with a shooting method, for the lowest multipoles, that is, l = 0, 1, and 2 for a massless scalar–tensor theory of the Brans–Dicke type, motivated by the R2 theory, and compare with those of a minimally coupled scalar field in general relativity. We consider a set of six realistic equations of state and extract universal relations for the modes.